POLA PERILAKU PENDAMPINGAN MENONTON TELEVISI OLEH IBU RUMAH TANGGA PADA PUTRAPUTRINYA - Asih Apriliani (IKOM UMY, 2015)
This study attempts to analyze how patterns of behavior homemaker assistance for their children in watching television, ethnographic study of audience porticipants on the housewives of media literacy training by the hlasyarokat Peduli lAedia (lvlPA4) at RT 04 ll Gatak, Tamantirto, Bantul, Yogyakarto. This ethnogrophic study uses the audience as the subject and the patterns of everyday subjects on which to base research. The purpose of this study was to exomine patterns of behavior homemaker assistonce and to determine the factors that influence it. This type of research focuses on observation and natural atmosphere (naturolistic settings), where researchers acted as observers. Researchers simply create categories of behavior, observed symptoms, and record observations in o book. Data collection techniques in this study using participant observations, in-depth interview, and documentation. The results showed a pattern of behavior homemaker assistance that include: restrictive mediation is a housewife sets the rules in the use of television on children, in the form of prohibition orders. Mentoring behovior patterns were found, caused by several factors, including: limitations of the mentoring period, the economy and access to information, setting the room watching television, Ievel of understanding of mentoring.